Using Compact Rio to measure and perform analysis on snow profile through a snowboard - Brooks, L.; Purdy, D. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: Using Compact Rio a standalone data logger to analyze snow profile felt through a snowboard while in use on both artificial and natural surfaces. To see if this form of data collection is suitable for further analysis on the rider to snowboard interaction and if it impedes the riders ability thus limiting the suitability of this method of testing.